Media relations and universities: an assessment of digital newsrooms. Issue 2 (3rd July 2018) - Lee, Nicole M.; Merle, Patrick F.
ABSTRACT: Reviews of editorial practices and academic studies have shown that journalists often rely on organization websites—and online newsrooms in particular—to inform news stories. Yet, at a time when many academics are called upon as experts by the media, university newsrooms have been ignored. To fill this gap, this study assesses newsrooms of universities to determine whether they are providing adequate resources to cover the institution or identify experts. Previous research demonstrated higher ranked Fortune 500 companies have more comprehensive newsrooms, potentially putting them at an advantage when it comes to news coverage. To better understand whether disparities exist among the top US institutions, this study features a content analysis of the newsrooms of the top 202 universities ranked by U.S. News & World Report . Findings show that although higher ranked universities typically feature more comprehensive newsrooms, universities at all levels are missing opportunities to provide journalists with information necessary to cover the university, thus limiting visibility to outside stakeholders. The most common features were internally written news stories and links to social media. Resources specifically for journalists were less common. Assessing newsrooms is valuable because they influence media coverage, which can improve credibility and perceived external prestige.